Cost‐Effectiveness of Osteoporosis Screening Using Biomechanical Computed Tomography for Patients With a Previous Abdominal CT. (24th March 2019) - Pisu, Maria; Kopperdahl, David L; Lewis, Cora E; Saag, Kenneth G; Keaveny, Tony M
ABSTRACT: Osteoporosis screening rates by DXA are low (9.5% women, 1.7% men) in the US Medicare population aged 65 years and older. Addressing this care gap, we estimated the benefits of a validated osteoporosis diagnostic test suitable for patients age 65 years and older with an abdominal computed tomography (CT) scan taken for any indication but without a recent DXA. Our analysis assessed a hypothetical cohort of 1000 such patients in a given year, and followed them for 5 years. Separately for each sex, we used Markov modeling to compare two mutually exclusive scenarios: (i) utilizing the CT scans, perform one‐time "biomechanical computed tomography" (BCT) analysis to identify high‐risk patients on the basis of both femoral strength and hip BMD T ‐scores; (ii) ignore the CT scan, and rely instead on usual care, consisting of future annual DXA screening at typical Medicare rates. For patients with findings indicative of osteoporosis, 50% underwent 2 years of treatment with alendronate. We found that BCT provided greater clinical benefit at lower cost for both sexes than usual care. In our base case, compared to usual care, BCT prevented hip fractures over a 5‐year window (3.1 per 1000 women; 1.9 per 1000 men) and increased quality‐adjusted life years (2.95 per 1000 women; 1.48 per 1000 men). Efficacy and savings increased further for higher‐risk patient pools, greater treatment adherence, and longer treatment duration. When the sensitivity and specificity of BCT were set to those for DXA, the prevented hip fractures versus usual care remained high (2.7 per 1000 women; 1.5 per 1000 men), indicating the importance of high screening rates on clinical efficacy. Therefore, for patients with a previously taken abdominal CT and without a recent DXA, osteoporosis screening using biomechanical computed tomography may be a cost‐effective alternative to current usual care. © 2019 American Society for Bone and Mineral Research.